The importance of wavelength for tight temperature control during µ-laser assisted machining - Dennis, Ashley; Goel, Saurav; Al-Sayegh, Rajab (Sage, 2020)
The area of single point diamond turning of brittle materials like semiconductors and ceramics is significantly benefitted by incorporation of laser assistance. In a new developmental technology that is now recognized as micro-laser-assisted machining (μ-LAM), a laser is shone through a diamond tool to soften the high-pressure phase transformed ductile machining phases that in turn allows thermal softening and thereby enables a higher material removal rate during ductile mode machining. One of the lasers currently used in μ-LAM is the neodymium-doped yttrium aluminum garnet (Nd:YAG) laser operating at 100 W (continuous wave) at the wavelength of 1064 nm. Although this configuration has worked to the benefit of the technology, here we report futuristic developments that will significantly enhance temperature control by selecting a laser wavelength according to the material being machined, allowing tunable machining properties. The concept is illustrated with sample calculations for μ-LAM of silicon, and it appears to offer better target temperatures, thus enhancing the performance of the μ-LAM process.
Keywords: hybrid machining; silicon; single point diamond turning; Micro-laser-assisted machining